Profile and career aspiration of Malaysian returnees - Ismail, Maimunah; Umar Baki, Nordahlia; Yeop Kamaruddin, Noor Ainun (Vilnius University Press, 2015)
This study examined profiles and predictors of career aspiration of Malaysian returnees from European and non-European countries. This study, involving 226 returnees, was carried out in the industrialized areas of the Klang Valley, Johore Bharu and Penang, and the state of Sabah. Based on the Social Cognitive Career Theory and the Chaos Theory of Careers the study derived personal and environmental factors within the major groups of push-pull factors that served as the predictors. Most returnees from Europe came back from the United Kingdom while Australia, Saudi Arabia, Japan, Korea and the United States were the host countries outside Europe. A regression analysis showed the explanatory power of career aspiration for returnees from European countries was higher (33.9%) than that of returnees from non-European countries (29.1%). Push political and pull social factors were significant for the former, whereas push social, pull personal and pull family factors were stronger for the latter ones. The implications of these findings for human resource practices and suggestions for future research are discussed.